The Sensitivity of The Human Sense of Touch (Skin) In The Qur'an - Ihsan, Sartika Fortuna; Elijonnahdi, Elijonnahdi; Nini, Nini (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This study aims to find out the wisdom behind the Qur'anic verses about skin sensitivity, both the pain felt by the skin contained in QS. An-Nisa' verse 56, and touch that can cause sexual arousal in QS. An-Nisa' 43 and the scientific clues of the phenomenon. This research uses a descriptive method in the form of library research. The results of this study are, Allah shows the truth of the Qur'an for people of reason that the Qur'an has discussed modern Anatomy issues since 1400 years ago, while modern scientists have only researched it with sophisticated equipment, this shows the high knowledge of Allah and at the same time as a warning to every human being, that every sin will get a painful reward like scorched skin and then exchanged back with new skin so that humans always feel very painful.